Patterns of Teacher-Students Interaction Based on The Textbook â€œWhen English Rings A Bellâ€ for Seventh Grade: A Classroom Discourse Study - Endang Poerbowarni (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aimed to: 1) describe how teachers structure their classroom interaction based on the textbook â€œWhen English Rings a Bellâ€ for Seventh Grade, and 2) reveal what affects their structuring classroom interaction.The study belongs to a case study. However, principles of discourse analysis are applied to data gathering and data analysis. Data were collected through interviews, document check, observation, note taking and videotaping of 80 minute-classroom interaction of four teachers, twice each, teaching seventh graders of four junior high schools. Verbal and non-verbal data were gathered, transcribed, noted and analyzed.Findings show that teachers structured their classroom interaction by consistently implementing the 2013 Curriculum and its aspects especially its scientific approach. More specifically, it was revealed that the teachers: (1) worked over the five stages of the scientific approach, in the order as it should be: observing, questioning, experimenting, associating, communicating; (2) started and ended the lessons using the same set of activities and expressions; (3) mostly used laptops and LCDs to provide language exposure by presenting songs, chants, texts, and tasks; (4) used Shawâ€™s textbook adaptation technique by modifying the content and format of the textbook material; (5) discussed interpersonal and transactional texts, through the textsâ€™ social function, generic structure, and linguistic features. (6) integrated all four language competences of listening, reading, speaking, and writing, with the emphasis on oral and written skills; (7) assigned tasks requiring studentsâ€™ active thinking rather that creative one; (8) were lack of time to measure studentsâ€™ individual performance; (9) used bilinguals of English and Indonesian; (10) conducted indoors classes and arranged students to sit facing them except in group works. Further it was found out that teachersâ€™ perception and language competence shaped teachersâ€™ presentation in similar and different classroom interaction.